PENGARUH MOTIVASI KONSELI DAN SIKAP EMPATI KONSELOR TERHADAP KEBERHASILAN PROSES KONSELING - Mudjijanti, Fransisca (Universitas Katolik Widya Mandala Surabaya Kampus Kota Madiun, 2012)
The effectiveness of problem solving through counseling can really be detected since the counselee begins to have a problem, namely when the counselee realizes that he has a problem. Counseling with people who are not aware of the problem is actually not effective. Counselee’s motivation to come to a counselor on the basis of awareness that he has a problem and is in need of someone else becomes a requirement of a successful guiding. In addition to the counselee’s motivation, another factor that influences the success of counseling is the counselor’s emphaty. A counselor’s ability to show emphaty is very important and indispensable to the success of counseling. The formulation of the problem of this study is as follows: 1. Is there a significant effect of counselee’s motivation on the success of counseling process? 2. Is there a significant effect of counselor’s empathy on the success of counseling process? 3. Is there a significant effect of counselee’s motivation and counselor’s empathy on the success of counseling process? The results of the correlation coefficient analysis showed that there was a great correlation between counselee’s motivation and counselor’s empathy and the success of counseling process as indicated by the correlation value 0.41-0.70 The analysis of determination coefficient showed that the success of counseling process was influenced by counselee’s motivation and counselor’s empathy by 23%. The result of t test showed that the first hypothesis, which reads